A Study on Reproductive Health Problems and Menstrual Hygiene Practices among Adolescent Girls Living in Slums of Guwahati city, Assam - Barthakur, Chinmayee; Barkataki, Monjuri (National Journal of Community Medicine, 2017)
Introduction: Reproductive health is an important aspect of adolescent health. Girls suffer from various reproductive health problems related to menstruation and reproductive tract infections, the extent of which is still underestimated. Objectives: This study was conducted with the objectives to assess reproductive health problems among adolescent girls living in slums and to assess menstrual hygiene practice among them. Methods: A community based cross sectional study was conducted among adolescent girls living in slums of Guwahati city. Multistage sampling technique was used for selecting the slums and after house to house visits adolescent girls aged 10-19 were included in the study. Results: Out of 119 adolescent girls 57.1% and 42.9% belong to 10-14 years and 15-19 years respectively. Overall 67.2% girls attained menarche. Majority 52.5% used sanitary pads during menstruation. Of the 119 girls, 20.2%, 24.4% and 9.2% presented with symptoms for RTI, UTI and for both RTI and UTI combined. Girls reported problems like dysmenorrhoea, UTI symptoms, and excessive vaginal discharge. Conclusion: Reproductive health problems are still common among adolescent girls and need urgent actions.